Information communication technologies [ concepts, methodologies, tools and applications - Van Slyke, Craig (Information Science Reference, 2008)
"This collection meets these research challenges; compiling breaking research in the pivotal areas of social adaptation to information technology. It covers ad-hoc networks, collaborative environments, e-governance, and urban information systems, case studies, empirical analysis, and conceptual models. Over 300 chapters contributed by experts, this six-volume compendium will provide any library's collection with the definitive reference on ICTs"--Provided by publisher.